Hylid frogs from Mount Ayanganna, Guyana: new species, redescriptions, and distributional records - MacCulloch, Ross D.; Lathrop, Amy (Phyllomedusa: Journal of Herpetology, 2005)
A new species of Osteocephalus, one species of Hyla, three species of Hypsiboas and one of Myersiohyla were collected on Mount Ayanganna, a sandstone Guiana Shield tepui. Hyla warreni, Hypsiboas roraima, H. sibleszi, Myersiohyla kanaima and the new Osteocephalus were collected in high-tepui forest at 1500 m elevation, while Hypsiboas lemai, H. roraima and M. kanaima were also collected in lower montane forest at 870 m. Supplementary descriptions of adults of all species of Hyla, Hypsiboas and Myersiohyla based on the newly collected specimens are provided. Tadpoles of M. kanaima are described. The specimens from Ayanganna represent significant distributional records for several species. This is the first record of Osteocephalus as a member of the Guiana Shield high-tepui herpetofauna.